PENERAPAN BLOCK DIENES UNTUK MENINGKATKAN HASIL BELAJAR BILANGAN CACAH SISWA KELAS III SEKOLAH DASAR - Amelia Gusman, Rayhana; M.Syahran Jailani; Sari, Tika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low mathematics learning outcomes of Grade III students at MI Nurul Ihsan, Jambi City, particularly in comparing whole numbers, where most students had not yet reached the Learning Objective Achievement Criteria (KKTP) of 78. This study aimed to describe the improvement in whole-number learning outcomes and to explain the process of using Dienes Blocks as a concrete instructional medium in mathematics learning for Grade III students. This research employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, implemented in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were all 21 Grade III students at MI Nurul Ihsan, Jambi City, in the 2025/2026 academic year. Data were collected through observation, learning outcome tests, interviews, and documentation, then analyzed descriptively using qualitative and quantitative approaches. The findings show that Dienes Blocks were effective in improving students' ability to compare whole numbers based on place value. In the pre-cycle stage, classical mastery reached only 24% with an average score of 54.3. After Cycle I, mastery increased to 52% with an average score of 71.7, while teacher activity reached 74% (sufficient) and student activity reached 62% (fairly active). In Cycle II, after adding place-value boxes as a supplementary medium, classical mastery increased significantly to 90% with an average score of 82.5, while teacher and student activity both reached 94% (very good/highly active). These results exceeded the success indicator of ≥75%, so the research was concluded at Cycle II. It is concluded that concrete media in the form of Dienes Blocks is highly effective for improving whole-number learning outcomes among third-grade elementary school students.